Formation et phylogénie des concepts de « marché » dans l’économie politique au xviiie siècle - Pascal Charbonnat (Revue de la Régulation)
How did the economists of the 18th century integrate the word “market” into their treatises? While the market is a matter for ordinary practices until the beginning of the 18th century, it becomes afterward an economic concept in several authors. To understand this change, a phylogeny of the market concepts is necessary, because the studies limited to one or two authors are not capable of following their formation process, necessarily polygenic. Through dictionaries, the ordinary practices of the market show two conceptions (serial and centred), which can be connected with two market scholar forms: a mere form (Cantillon, Turgot and Morellet) and a developed form (Smith and Condillac). These links must be combined with the previous conceptions of the value, to propose a meshing not linear phylogenic. We can conclude that the metaphysical concepts relative to the providence did not participate in the formation process of the market scholar concepts.